HUBUNGAN KONTROL DIRI DENGAN PRILAKU KERJA KONTRAPRODUKTIF PADA PT. AGRA BUMI NIAGA (ABN) ACEH - Sinarsi Meliala; Dwi Nursiti; Indo Mora; Siti Nurliza Amri (JURNAL PSYCHOMUTIARA, 2020)
The growing wordl of organization and their strict competition is one of the factors to demand resources in it to be more actively developed in accordance with yhe organization standars that have been established. The advancement of community mindsets demamd that every organization to improve service Standaar for its costomers, such as government organizations that move on government duties. This study aims to determine how the relationship between self-control and counterproductive work behavior at PT. Agra Bumi Niaga (ABN) Aceh. This study uses the correlation method which is astudy that points to the concept of interrelation between several variables, the simplest correlation involves only two variables. The population in this study were all employees of PT. Agra Bumi Niaga totaling 168 employees with a sampel of 118 employees. Data collection techniques used by questionnaire media, and interview method. Data analysis techniques in this study used correlation regression analysis. The results of this study indicate that there is a significant relationship between self- control and counterproductive work behavior at PT. Agra Bumi Niaga Aceh. Relationships that are categorized as strong /high correlation, this can be proven based on the results of the calculation of the correlation test with a significant value = 0,907. The higher self-control in employees, the lower the counterproductive work behavior of eployees at PT. Agra Bumi Niaga Aceh. Thereby in anticipating low self-control and high counterproductive employees, PT ABN Aceh is expected to provide seminars on self-control in its employees so as to improve self control and improve control themselves in a working envioronment in order to make to make a positive impact on themselves and others.